2018
DOI: 10.1017/ice.2018.292
|View full text |Cite
|
Sign up to set email alerts
|

Human factors–based risk analysis to improve the safety of doffing enhanced personal protective equipment

Abstract: ObjectiveTo systematically assess enhanced personal protective equipment (PPE) doffing safety risks.DesignWe employed a 3-part approach to this study: (1) hierarchical task analysis (HTA) of the PPE doffing process; (2) human factors-informed failure modes and effects analysis (FMEA); and (3) focus group sessions with a convenience sample of infection prevention (IP) subject matter experts.SettingA large academic US hospital with a regional Special Pathogens Treatment Center and enhanced PPE doffing protocol e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…[13] Although more complex than the PPE ensembles used in transmission-based precautions, human factors analyses of the doffing process for enhanced PPE ensembles used to care for patients with EVD, have highlighted numerous opportunities for PPE failure and self-contamination. [3] Gurses et al [14] concluded that safe doffing of PPE requires knowledge, skills and attitudes, not just instructions for the sequence and technique for how to remove pieces of PPE. Our observations suggest that HCWs are not familiar with the sequence and technique for how to remove pieces of PPE, but training that builds knowledge and skills and changes attitudes may motivate HCWs to utilize the correct sequence and technique.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Although more complex than the PPE ensembles used in transmission-based precautions, human factors analyses of the doffing process for enhanced PPE ensembles used to care for patients with EVD, have highlighted numerous opportunities for PPE failure and self-contamination. [3] Gurses et al [14] concluded that safe doffing of PPE requires knowledge, skills and attitudes, not just instructions for the sequence and technique for how to remove pieces of PPE. Our observations suggest that HCWs are not familiar with the sequence and technique for how to remove pieces of PPE, but training that builds knowledge and skills and changes attitudes may motivate HCWs to utilize the correct sequence and technique.…”
Section: Discussionmentioning
confidence: 99%
“…The doffing sequence is the reverse. Improper use of PPE is known to spread infection among health care workers [ 4 , 5 ]. All these steps can be sources of errors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on using full PPE in various contexts (chemical, biological, radiological, nuclear and explosive incidents, firefighting, health care, and the military) has shown several human factor problems. Much of the research addressed procedural problems, including failures to effectively put on (don) or remove (dof) the PPE [ 2 - 5 ], and ergonomic problems such as poor fit and discomfort while having it on [ 6 - 9 ]. Problems of ineffective use or decreased adherence to using the PPE were found to be associated with insufficient training and lack of prior experience [ 10 - 13 ], and with the appropriateness of organizational culture [ 12 , 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that PPE should be redesigned in ways that facilitate expedient and safe doffing methods. Design cues could help HCWs envision and execute appropriate doffing methods; for example, color-coding PPE surfaces to differentiate “dirty” outside surfaces from “clean” inside surfaces could help HCWs track where these surfaces are at each step of the doffing process [16, 27]. Fasteners (eg, straps, belts) that do not require untying and are easy to undo (or rip) quickly would facilitate speed and ease of doffing [16, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Design cues could help HCWs envision and execute appropriate doffing methods; for example, color-coding PPE surfaces to differentiate “dirty” outside surfaces from “clean” inside surfaces could help HCWs track where these surfaces are at each step of the doffing process [16, 27]. Fasteners (eg, straps, belts) that do not require untying and are easy to undo (or rip) quickly would facilitate speed and ease of doffing [16, 27]. PPE also must fit people of different sizes and physical abilities and should be either adjustable or available in several sizes [14, 27].…”
Section: Discussionmentioning
confidence: 99%